Factors affecting educational tourism development among local communities in the Klang Valley, Malaysia - Abu Samah, Asnarulkhadi; Ahmadian, Maryam; Gill, Sarjit S.; Hendijani, Roozbeh Babolian (Marsland Press, 2012)
The purpose of this study is to examine factors influencing educational tourism development among local communities in Malaysia. The results denote that socio-cultural impact, economic impact, and local community attitudes towards educational tourism were significantly related to residents’ practice and communication with international students. In addition, residents’ attitude can affect local communities’ interaction with international students more than other variables. Since educational tourism plays an increasingly important role in the development of communities in Malaysia, the implications of this study provide new insights into future researches by highlighting this current challenge.